(9b² - 4c²)/(12b²c - 8bc²) = ((3b)² - (2c)²)/(4bc(3b - 2c)) =
(3b - 2c)(3b+2c)/(4bc(3b - 2c)) = (3b+2c)/4bc = (3·1/3 + 2·(-6))/(4·1/3·(-6)) =
-3·(1 - 12)/24 = 3·11/24 = 11/8 = 1,375
Ответ:
1,375
Пошаговое объяснение:
(9в²-4с²)/(12в²с-8вс²)=(3в-2с)(3в+2с)/4вс(3в-2с)=(3в+2с)/4вс
(3*1/3 + 2*(-6))/(4*1,3*(-6))=(1-12)/-8=11/8=1,375
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
(9b² - 4c²)/(12b²c - 8bc²) = ((3b)² - (2c)²)/(4bc(3b - 2c)) =
(3b - 2c)(3b+2c)/(4bc(3b - 2c)) = (3b+2c)/4bc = (3·1/3 + 2·(-6))/(4·1/3·(-6)) =
-3·(1 - 12)/24 = 3·11/24 = 11/8 = 1,375
Ответ:
1,375
Пошаговое объяснение:
(9в²-4с²)/(12в²с-8вс²)=(3в-2с)(3в+2с)/4вс(3в-2с)=(3в+2с)/4вс
(3*1/3 + 2*(-6))/(4*1,3*(-6))=(1-12)/-8=11/8=1,375